The journey from Corporate Social Responsibility to Corporate Social Innovation: The Whys and the Hows - Nazari, Mohsen; Nezami, Iman Mostashar; Zargar, Zoha Haji Ebrahim (Technium Business and Management, 2022)
On the path to industrialization, companies sought to create value for customers, shareholders, and owners. The relentless pursuit of profitability violated the rights of some community members and provoked several protests against the violation of human rights and negligence of environmental issues. Companies first understood these problems and accepted the demands of stakeholders. However, following the closure of many businesses that were not socially responsible, companies decided to apply general principles to create a good social image. Therefore, they stopped the protests against them by preventing the emergence of social problems and severe consequences of companies’ actions towards society and nature. These events led to the introduction of the concept of corporate social responsibility (CSR). Accordingly, companies attempted to take action and create a good social image of themselves by spending some money before being obliged by the law and society to deal with the negative social and environmental consequences of their activities. The problem was that companies spent only part of their profits on projects that they thought would receive the most significant social feedback. However, in traditional charitable CSR efforts, it is often impossible to undertake an activity and measure its tangible social outcomes in the long run. Companies must pursue a strategic concept that produces sustainable social changes by engaging different company segments and stakeholders. This concept is called corporate social innovation (CSI). This study defined the concept of CSR and showed how the definitions and concepts and corporate trends have shifted from CSR to CSI over the course of time.